Diabetic autonomic neuropathy is a barrier to achieving glycemic control - A. F. Verbovoy (Медицинский совет, 2020)
Diabetic autonomic neuropathy is the second most common form of damage to the nervous system in diabetes mellitus as a result of disorders of the central and/or peripheral parts of the autonomic nervous system. On average, its frequency of occurrence is about 40%, and 60% or more with an increase in the duration of diabetes over than 10 years. Diabetic autonomic neuropathy is characterized by polysyndromism of clinical manifestations. In this regard, a number of forms of diabetic autonomic neuropathy are distinguished both in the form of an isolated violation of the function of organs and systems, and with their combined defeat. In the pathogenesis of autonomic neuropathy, vascular and metabolic changes common to the development of diabetic polyneuropathy play an important role. The most significant risk factors for the development of diabetic autonomic neuropathy are the patient's age, duration of diabetes mellitus, and a higher average HbA1c. The development and progression of diabetic autonomic neuropathy depends on glycemic control, but its forms such as gastrointestinal and impaired recognition of hypoglycemia (asymptomatic hypoglycemia) can cause poor compensation for diabetes. This article discusses the various clinical manifestations of gastrointestinal autonomic neuropathy. Attention is drawn to the fact that the clinical picture is often nonspecific and asymptomatic, which complicates timely diagnosis. The gastrointestinal form of diabetic autonomic neuropathy leads to limited performance, social maladaptation of patients, dramatically reduces the quality of life of patients with diabetes mellitus. In clinical practice, the doctor must remember that it can significantly affect the achievement of glycemic control, as a result of a violation of the digestion and passage of food, as well as a violation of the pharmacokinetics of hypoglycemic drugs. Impaired recognition of hypoglycemia also makes it difficult to compensate well. These complications require a personalized approach to the patient from the doctor, and strict and frequent self-control of glycemia with the help of a modern glucometer from the patient to maintain optimal glycemic control and prevent possible hypoglycemic conditions.